Novel biocatalytic strategy of levan: His-ELP-intein-tagged protein purification and biomimetic mineralization. (15th July 2022) - Zhang, Yifeng; Gao, Song; Qi, Xianghui; Zhu, Song; Xu, Shumin; Liang, Yaokun; Kong, Fanshu; Yang, Shuai; Wang, Rui; Wang, Yiting; An, Yingfeng
Abstract: Here a versatile fusion tag composed of His-tag, intein, and elastin-like polypeptide (ELP) tag was prepared for the first time to be fused with levansucrase SacB to construct a recombinant His-ELP-intein-SacB (HEIS) protein to realize nonchromatographic purification of SacB. The efficient biomimetic mineralization of CaHPO4 and HEIS-based hybrid-hydrangea (CaHPO4 -HEIS-HH) with good reusability, excellent storage stability and 254.3% improved relative levan yield was prepared with the biomimetic mineralization method. Additionally, the CaHPO4 -HEIS-HH showed outstanding operation activity when catalyzing sucrose in solution and up to 75% sucrose conversion rate in fruit juices. The mechanism of biomimetic mineralization was analyzed to show that the HEIS protein might serve as a "binder" to assemble the nanoflakes during biomimetic mineralization. The CaHPO4 -HEIS-HH was applicable for efficient production of the levan-type prebiotic polysaccharides, and this approach should be highly valuable for nonchromatographic purification and convenient preparation of various encapsulated enzymes for more efficient catalysis. Graphical abstract: Unlabelled Image Highlights: A strategy was designed for more efficient nonchromatographic purification of protein. CaHPO4-based biomimetic mineralization of SacB was designed for improved catalysis. The resulting CaHPO4-HEIS-HH was useful for efficient production of prebiotic levan. CaHPO4-HEIS-HH showed up to 75% sucrose conversion within fruit juices of pH 3.0–5.0. The principle of CaHPO4-based biomimetic mineralization was deeply analyzed.